How Civil Servants Frame Participation: Balancing Municipal Responsibility With Citizen Initiative in Ede’s Food Policy - van de Griend, Joëlla (2019)
Contemporary governance is marked by increased attention for participation of non-governmental actors (NGAs) in traditionally governmental activities, such as policy-making. This trend has been prevalent across food policy processes and reflects a key feature of food democracy. However, the role of governmental actors in facilitating and responding to this participation remains a gap in the literature. In this article, we ask how civil servants frame the participation of NGAs in policy processes. Drawing on ethnographic research, we introduce the case of civil servants working on an urban food policy for the municipality of Ede (the Netherlands). Our analysis uncovers two competing frames: 1) highlighting the responsibility of the municipality to take a leading role in food policy making, and 2) responding reflexively to NGAs. The analysis provides insights into how the framing of participation by civil servants serves to shape the conditions for participation of NGAs. It further sheds light on related practices and uncovers existing tensions and contradictions, with important implications for food democracy. We conclude by showing how, in the short term, a strong leadership role for civil servants, informed by the responsibility frame, may be effective for advancing policy objectives of the municipality. However, the reactive frame illustrates that civil servants worry this approach is not effective for maintaining meaningful participation of NGAs. This remains a key tension of participatory municipal-led urban food policy making, but balancing both municipal responsibility and an open and reactive attitude towards the participation of NGAs is useful for enhancing food democracy.